IMPLEMENTASI SISTEM PEMANTAUAN JARINGAN MENGGUNAKAN LIBRENMS PADA JARINGAN KAMPUS UNIVERSITAS UDAYANA - Krisna Saputra, I Wayan; Wiharta, Dewa Made; Putra Sastra, Nyoman (Jurnal SPEKTRUM; Vol 7 No 2 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i02.p11, 2020)
Udayana University is education institutions that has implemented an online learning system. The system requires fast and reliable access to internet so students can access them efficiently. In order to meet the need for internet access, it requires to provide infrastructure that is able to keep internet services running smoothly. Network Monitoring requires an application called Network Monitoring System. There are many network monitoring applications available for free, which provides many option for network operators to carry out monitoring functions. LibreNMS is a popular application because LibreNMS has many features, such as: autodiscovering, flexible and diverse alerting system, comfortable user interface with a dashboard that can be adjusted to user needs and has wide community support. LibreNMS allows network administrators to monitor performance on the network so that it is always available. This study aims to build a network monitoring system on the Sudirman Campus of Udayana University using LibreNMS. The test results show that LibreNMS is able to display traffic conditions and resource usage on every network device that is monitored.